IMPLEMENTATTION OF CHILDREN’S FRIENDLY SCHOOL POLICY TO TACKLE THE CULTURE OF BRAWL IN THE MIDDLE SCHOOL (SMA) IN DKI JAKARTA - Herlina, Lina; Suryana, Asep (EARR (Educational Administration Research and Review), 2018)
The purpose of this study is to identify the fight against brawl culture in high schools (SMA) through the implementation of character education in the Child Friendly School policy. The approach used is qualitative with the object of research teachers and principals. Data collection in this study uses interviews, observation and recommendation studies. Based on research results found that through good character education management that involves teachers and principals as examples in the application of character education, it can encourage students not to fight.